Siyāsah Shar'iyyah and the Politicization of Religion in the 2019 Indonesian Presidential Election - Zainuddin, Zainuddin; Efendi, Roni; Mirdad, Jamal; Yaacob, Salmy Edawati (Universitas Islam Negeri Jakarta, 2022)
The politicization of religion in general elections has been a global issue in both religious and secular countries. Since 1955 to 2019, Indonesia experienced political contests laden with religious attributes, which sparked conflicts. This research aims to analyze the relevant issues and motives associated with using religious elements in the presidential election campaign 2019. This study is empirical research and involves interviews with high-level officials of political parties. Furthermore, the online mass media, official blogs of candidate pairs for president and vice president, and social media were employed as secondary data. Following the analysis, the result implies that the politicization of religion in the 2019 presidential election campaign firmly appears amidst the decline of presidential and vice presidential candidates' religious polarization. The use of religious issues in the campaign yielded public sympathy and antipathy, affecting the electability of presidential and vice presidential candidates. Meanwhile, counter-elements contradict negative images that discredit presidential and vice presidential candidates. The motives for politicizing religion were identified as